Closing the Implementation Gap of Nature-based Solutions: The case of Water as Leverage - Cascading Semarang - Jaimerena, Begonia (Journal of Delta Urbanism, 2022)
Nature-based Solutions (NbS) can help cities to become more resilient and climate adaptive. But more often than not, their implementation is reduced to awareness-raising pilot projects with limited chances of upscaling. The strategic plans that integrate these solutions, are hardly translated into investment plans, creating an implementation gap for NbS. The Water as Leverage – Cascading Semarang project, addressed this gap as part of the development of an innovative, sustainable, bankable and implementable design proposal that considers an inclusive approach. It started with a shared narrative that defined a theory of change, through the development of the full investment case and implementation strategies. The lessons learnt from that project, showed the urban planners and designers are in a unique position to drive the process of closing the implementation gap. Their comprehensive understanding of the urban dynamics, paired with the skills to lead the development of an innovative vision and shared narrative, can trigger the transformative changes that are needed to face current and future urban challenges. Furthermore, a collaborative approach enables ownership and allows the integration of relevant knowledge throughout the process, including environment, finance, and society.